Fiber architecture in the human ventromedial striatum and its relation with the bed nucleus of the stria terminalis - Oliver Krüger; Uwe Klose; Gisela E. Hagberg; Thomas Shiozawa-Bayer; Henry Evrard; Cintia Meszaros; Thomas Ethofer; Klaus Scheffler; Ulrike Ernemann; Benjamin Bender (PLoS ONE, 2025)
The bed nucleus of the stria terminalis (BST) and the ventromedial striatum (consisting of the head of the caudate nucleus (hCN) and the nucleus accumbens (NAcc)) are both part of complex, foremost limbic networks involved in a variety of neuropsychiatric conditions. However, data on functional or structural connections between the BST and hCN in humans are scarce. In an earlier study using both diffusion tensor magnetic resonance imaging (DTI) and conventional histology we found a pathway from the BST to the orbitofrontal cortex apparently passing directly through the hCN. To confirm this finding, we now examined the hCN in human ex-vivo brain tissue using polarized light microscopy (PLM), a method particularly suitable for depicting myelinated nerve fibers. We further examined whether differences in fiber distribution inside the hCN could be depicted using high-resolution DTI data. PLM revealed different fiber populations inside the hCN and the NAcc. Fibers in the hCN were mostly related to the anterior limb of the internal capsule (ALIC) with some apparently terminating in the hCN while the majority exited the hCN to enter the prefrontal white matter. Fibers originating from the BST were only scarcely seen on this level and appeared to either terminate inside the hCN or join the ALIC. On levels below the anterior commissure, the BST strongly connected 1) to other basal forebrain structures including the NAcc, and 2) with the white matter of the medial prefrontal cortex. Differences in fiber density within the hCN could be reproduced on MRI data but with strong interindividual variation. In summary, PLM revealed a much more complex fiber architecture in the region of interest than suggested by our earlier DTI findings. The study at hand shows that PLM can be a valuable tool for the verification of unclear or ambiguous DTI fiber tracking results.